Analysis of the Linkage Between Concepts, Theory, and Research - Inkaew, Thayuta; Taiwong, Anucha; Settheekul, Saowaluck (NU Journal of Nursing and Health Sciences, 2025)
Nursing research is a systematic process of inquiry based on empirical research methodologies to develop nursing knowledge, encompassing nursing practice, education, and administration. Theory-linked research involves utilizing existing nursing theories as frameworks for conducting research. The goal is to test these theories or generate new ones that contribute useful, generalizable knowledge to nursing. However, theories are composed of relatively abstract concepts and propositions. Researchers must analyze and deduce these abstract statements into concrete terms to design effective and credible research. This article illustrates methods for analyzing the relationships between concepts, theories, and research. These methods include Gibbs’s model of substruction, Hinshaw’s theoretical substruction, and Fawcett’s conceptual-theoretical-empirical structure. These methods can help researchers gain insight into the relationships between concepts, theories, and the determination of research variables and instruments. Consequently, the researchers can develop effective empirical research methodologies that align with theories and are practical for their research projects.